ASUPAN GIZI ANAK BALITA PESERTA POSYANDU - Hadi Riyadi; Dadang Sukandar (Jurnal Gizi dan Pangan, 2009)
The objectives of this action research were: (1) to assess nutritional status of children under five years under five years under five yaers, and (2) to evaluate the effects of nutrition education and home gardening to nutritional status of children under five years under five years. The research was carried out in two sub-districts of Bogor: Sub-District of Ciomas and Sub-District of Darmaga. This research started with a preliminary study as the first step and experimental design as the second step.  As many as 16 posyandu  that met research requirements were obtained. A total number of 240 mothers had been divided into kontrol and intervention groups.Collected data included the data of household, children under five years under five years and mothers. Baseline data were collected during the pre-study, while endline data were collected after conducting intervention (experiment). The experiment had been conducted for five months in the form of providing  nutrition education once intwo weeks and implementing home gardening. The data analysis included estimation of mean, standard deviation, minimum value, maximum value and proportion. The estimation results were then presented in tables and diagrams.Based on the analysis of nutrition intake data, it appears that intervention of nutrition education and home gardening has given great impacts on macronutrient and micronutrient improvement. The impacts of this nutrition intake improvement are not only because of the availability of vegetable garden in their home, but also because of the allocation of the family resources that is aimed at buying nutritious food. This has proved that knowledge about giving appropriate food is a prerequisite to improve access and sufficient and nutritious food, which has become a basis to reduce any kind of malnutrition.